Report for Establishing BPO Company X - Hasan, Ahmed; Efue, Barbara; Visaria, Rachit (2010)
There are many people who are very passionate about their hobbies and eventually convert those hobbies into businesses. Often, they lack the expertise required to transform these businesses into a faster growing organization. Our research focused specifically on football and Rugby Amateur sports clubs. We have identif ied the challenges currently faced with the running of these clubs as well as drawn out a list of services that can be outsourced to a Business Process Outsourcing (BPO) Company. These services are majorly administrative and are intended to give sports clubs the opportunity not only to focus more on their passion but at the same time grow more professional businesses. The foundation for this research was provided by four entrepreneurs who intend to set up a new BPO Company that would cater to the needs of passionate SMEs. Efforts have therefore been made to incorporate a business model, business plan and Implementation plan that could be adopted by this BPO Company. To ensure a realistic output, an indepth market analysis was undertaken. For our methodology, we have utilized a combination of extensive desk-top research, Interviews and academic journals and articles. The concepts reviewed in our literature review section form the basis for all our analysis. Our findings indicate that there is indeed a desire by passionate SMEs to outsource some business activities. However, they are open to this option only to the extent that it results in time and cost savings; as well as improve business efficiency. We conclude be making recommendations that would prove useful to a BPO Company that wishes to provide offerings to passionate SMEs.